The secret seven : Good old secret seven - Blyton, Enid. (b, 2004)
There are strange happenings at Torling Castle. Who is lurking in the ruined tower - and why have the resident jackdaws been disturbed?
Keywords: Secret Seven (Fictitious characters) -- Juvenile fiction; Castles -- Juvenile fiction. -- England; Theft -- Juvenile fiction